2017
DOI: 10.18203/2394-6040.ijcmph20170272
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between frequency of fogging focus and incidence of dengue hemorrhagic fever cases in Bandung in year 2010-2015

Abstract: Background: Incidence rate of dengue hemorrhagic fever (DHF) in Bandung city is still considerably high over the years. There is no well-documented example of the effectiveness of fogging focus and there is no data on fogging focus activities that have been undertaken by Dinas Kesehatan Kota Bandung. Therefore, this study aims to analyze the relationship between frequency of fogging focus and incidence of DHF cases in Bandung from year 2010 to 2015.Methods: An analytical observational study with cross sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Space spraying has little effect on the mosquito population, and thus on dengue transmission [4]. In Asia and America, studies have shown that after application of the ultra-low volume spray, the density of the adult population of Aedes mosquitoes returned to the pre-treatment level within 2 weeks and even with multiple applications, the impact of the spray was minimal [5]. The most annoying report on fogging has come in from the city of Bandung, Indonesia.…”
Section: Resultsmentioning
confidence: 99%
“…Space spraying has little effect on the mosquito population, and thus on dengue transmission [4]. In Asia and America, studies have shown that after application of the ultra-low volume spray, the density of the adult population of Aedes mosquitoes returned to the pre-treatment level within 2 weeks and even with multiple applications, the impact of the spray was minimal [5]. The most annoying report on fogging has come in from the city of Bandung, Indonesia.…”
Section: Resultsmentioning
confidence: 99%
“…DHF cases in Malang Regency in 2017 were 451 cases, an increase of 682 cases in 2018 (BPS, 2018). Efforts made by the government through the health department are the fogging program (Yee et al, 2017), larvae eradication using abate (Suriami et al, 2020), cypermethrin (A. P. de Araujo et al, 2019) as a vector control program.…”
Section: Methodsmentioning
confidence: 99%
“…It is done in the area around the patient's house until the radius of 100 -200 meters. Some studies have demonstrated the effectiveness of fogging in increasing the percentage of free larvae and reducing the percentage of larvae [12,30] However, fogging with malathion only kills adult mosquitoes, and it does not kill the existing larva, so the larva in the target area can still develop into adult mosquito. However, not all larvae that develop into adult mosquitoes carry dengue virus.…”
Section: Detection Of Dengue Virus In Male and Female Aedes Aegypti Mmentioning
confidence: 99%